Perumusan Strategi Bersaing Melalui Pendekatan Analisis Swot Pada Toko P&D H.Allex Padang - Irfan Dwi Wahyu Irwan; Yofina Mulyatib (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2025)
P&D H. Allex Padang Shop is a shop that sells various daily necessities. The purpose of this study is to determine the internal and external environmental factors that affect the store and to find out the competitive strategies used in increasing sales. The type of research used in this study is descriptive with a qualitative approach. Data collection methods using observation, interviews and documentation conducted on related parties at the P&D H. Alleix Padang Store. The data that has been obtained is analyzed using the EFE, IFE, SWOT, IE and QSPM matrices. The results of the EFE Matrix are 3.109 and the IFE Matrix is ​​2.990. The results of the IE Matrix show quadrant II and the intensive strategies in this quadrant, namely market penetration, market development and product development or integration, namely forward integration, backward integration and horizontal integration can be the most appropriate. The final results of this study conclude that the recommendation or proposal for the right competitive strategy for the store obtained based on the results of data processing through the QSPM matrix is ​​Market Peìneìtration with a score of 6.52. This strategy is used to improve product quality to provide guarantees to customers, establish good cooperation with suppliers, increase online sales and utilize technology, maintain good relationships with customers and determine and maintain market pricing strategies to face competition.